FGF1 Protects MCF-7 Cells against Taltobulin through Both the MEKs/ERKs and PI3K/AKT Signaling Pathway - Jakub Szymczyk; Aleksandra Czyrek; Jacek Otlewski; Malgorzata Zakrzewska (Biomedicines, 2023)
Breast cancer is a widespread and complex disease characterized by abnormal signaling pathways that promote tumor growth and progression. Despite significant medical advances and the development of increasingly effective therapies for breast cancer, drug resistance and reduced sensitivity to prior therapies remain persistent challenges. Dysregulation of growth factors such as FGFs and EGF and their receptors is a contributing factor to reduced response to treatment, promoting cell survival and proliferation, metastasis, EMT or increased expression of ABC transporters. Our study demonstrates a protective role for FGF1 in MCF-7 breast cancer cells against taltobulin-induced cytotoxicity, mediated by activation of its receptors and compares its activity to EGF, another growth factor involved in breast cancer development and progression. The mechanisms of action of these two proteins are different: FGF1 exerts its effects through the activation of both ERKs and AKT, whereas EGF acts only through ERKs. FGF1 action in the presence of the drug promotes cell viability, reduces apoptosis and increases cell migration. Although EGF and its receptors have received more attention in breast cancer research to date, our findings highlight the key role played by FGFs and their receptors in promoting drug resistance to tubulin polymerization inhibitors in FGFR-positive tumors.